Capability, opportunity, and motivation to enact hygienic practices in the early stages of the COVID‐19 outbreak in the United Kingdom. Issue 4 (16th May 2020) - Gibson Miller, Jilly; Hartman, Todd K.; Levita, Liat; Martinez, Anton P.; Mason, Liam; McBride, Orla; McKay, Ryan; Murphy, Jamie; Shevlin, Mark; Stocks, Thomas V. A.; Bennett, Kate M.; Bentall, Richard P.
Abstract : Objectives: The COVID‐19 pandemic is one of the greatest global health threats facing humanity in recent memory. This study aimed to explore influences on hygienic practices, a set of key transmission behaviours, in relation to the Capability, Opportunity, Motivation‐Behaviour (COM‐B) model of behaviour change (Michie et al., 2011). Design: Data from the first wave of a longitudinal survey study were used, launched in the early stages of the UK COVID‐19 pandemic. Methods: Participants were 2025 adults aged 18 and older, representative of the UK population, recruited by a survey company from a panel of research participants. Participants self‐reported motivation, capability, and opportunity to enact hygienic practices during the COVID‐19 outbreak. Results: Using regression models, we found that all three COM‐B components significantly predicted good hygienic practices, with motivation having the greatest influence on behaviour. Breaking this down further, the subscales psychological capability, social opportunity, and reflective motivation positively influenced behaviour. Reflective motivation was largely driving behaviour, with those highest in reflective motivation scoring 51% more on the measure of hygienic practices compared with those with the lowest scores. Conclusions: Our findings have clear implications for the design of behaviour change interventions to promote hygienic practices. Interventions should focus on increasing and maintaining motivation to act and include elements that promote and maintain social support and knowledge of COVID‐19 transmission. Groups in particular need of targeting for interventions to increase hygienic practices are males and those living in cities and suburbs.